1984
DOI: 10.1007/bf00383532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ruv mutations on recombination and DNA repair in Escherichia coli K12

Abstract: Mutation of the ruv gene of E. coli is associated with sensitivity to radiation, and filamentous growth after transient inhibition of DNA synthesis. The filamentation of ruv strains is abolished by mutations in sfiA or sfiB that prevent SOS induced inhibition of cell division, but this does not restore resistance to UV radiation. Double mutants carrying both ruv and uvr mutations are considerably more sensitive to UV radiation than the single mutants, but there is no additive effect of ruv with recA, recF, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(105 citation statements)
references
References 41 publications
3
102
0
Order By: Relevance
“…This observation runs counter to the common view of RuvABC being a resolvasome (60), which is supported by considerable data; the phenotypes of mutations in ruvA, ruvB, and ruvC are similar (61,62). Monoclonal antibodies against RuvA, RuvB, or RuvC inhibit resolution of a HJ in a reconstituted branch migration system (60).…”
Section: Discussionmentioning
confidence: 69%
“…This observation runs counter to the common view of RuvABC being a resolvasome (60), which is supported by considerable data; the phenotypes of mutations in ruvA, ruvB, and ruvC are similar (61,62). Monoclonal antibodies against RuvA, RuvB, or RuvC inhibit resolution of a HJ in a reconstituted branch migration system (60).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, we concluded that the ruv-53 mutation is distinct from the ruvA and ruvB mutations; this is in agreement with the report by Sharples et al (25), who showed that the ruv-SJ and ruv-53 mutations are complemented by the plasmids carrying the chromosomal fragments upstream of the ruvAB operon. They designated these mutations ruvC, because their phenotypes are very similar to those of ruvB and ruvAB mutants; i.e., ruvC mutants are sensitive to DNA-damaging agents and are defective in recombination when they carry additional mutations in recBC sbcA or recBC sbcBC (11,12).…”
Section: Resultsmentioning
confidence: 99%
“…CS40a (11) was used as a ruv+ control strain. The Ruv phenotype was examined by the sensitivity of the mutant to UV irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses indicate that RuvC resolvase plays a defined role in processing recombination and repair intermediates (7)(8)(9)(10)(11). In vitro studies confirm that RuvC specifically interacts with and resolves Holliday junctions by endonucleolytic cleavage (12,13).…”
mentioning
confidence: 94%